2017
DOI: 10.1002/acm2.12134
|View full text |Cite
|
Sign up to set email alerts
|

Adapting VMAT plans optimized for an HD120 MLC for delivery with a Millennium MLC

Abstract: Linac downtime invariably impacts delivery of patients' scheduled treatments. Transferring a patient's treatment to an available linac is a common practice. Transferring a Volumetric Modulated Arc Therapy (VMAT) plan from a linac equipped with a standard‐definition MLC to one equipped with a higher definition MLC is practical and routine in clinics with multiple MLC‐equipped linacs. However, the reverse transfer presents a challenge because the high‐definition MLC aperture shapes must be adapted for delivery w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…A study by Height et al [ 23 ] investigated the effect of different leaf widths from Varian on the treatment of early breast cancer and found no clinically significant differences using 5 mm vs. 10 mm MLC leaf widths. A previous study by French et al [ 24 ] investigated transferring a high-definition MLC (14-32-14 pattern of widths 5-2.5-5 mm) VMAT plan to Millennium MLCs (10-40-10 pattern of widths 10-5-10 mm) and found that a high-definition MLC had a smaller area for a given control point. In addition to differences in leaf numbers and widths, Trilogy and Synergy differ in jaw movement and dose rate bins.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Height et al [ 23 ] investigated the effect of different leaf widths from Varian on the treatment of early breast cancer and found no clinically significant differences using 5 mm vs. 10 mm MLC leaf widths. A previous study by French et al [ 24 ] investigated transferring a high-definition MLC (14-32-14 pattern of widths 5-2.5-5 mm) VMAT plan to Millennium MLCs (10-40-10 pattern of widths 10-5-10 mm) and found that a high-definition MLC had a smaller area for a given control point. In addition to differences in leaf numbers and widths, Trilogy and Synergy differ in jaw movement and dose rate bins.…”
Section: Discussionmentioning
confidence: 99%
“…The Edge linear accelerator utilizes a high definition 120 multi‐leaf collimator (MLC) with 120 leaves as well. The MLC configuration consists of 64 central leaves with a projection leaf width of 0.25 cm at the isocenter, while the remaining 56 outer leaves have a projection leaf width of 0.5 cm 26 . In our investigation, we conducted a comprehensive 12‐week comparative analysis utilizing two distinct evaluation methods: the Gamma index test and an enhanced variant of the SSI, denoted as SSI* in this paper.…”
Section: Methodsmentioning
confidence: 99%
“…The MLC configuration consists of 64 central leaves with a projection leaf width of 0.25 cm at the isocenter, while the remaining 56 outer leaves have a projection leaf width of 0.5 cm. 26 In our investigation, we conducted a comprehensive 12‐week comparative analysis utilizing two distinct evaluation methods: the Gamma index test and an enhanced variant of the SSI, denoted as SSI* in this paper. The delivery approach encompassed both a static and a VMAT technique employing the picket fence pattern.…”
Section: Methodsmentioning
confidence: 99%